Incidence rates and clinical Symptoms of Salmonella, Vibrio parahaemolyticus, and Shigella infections in China, 1998–2013 - Qi, Xu Lin; Wang, Hai Xia; Bu, Shu Rui; Xu, Xiao Gang; Wu, Xiao Yan; Lin, Dong Fang (The Journal of Infection in Developing Countries, 2016)
Introduction: The etiological and clinical characteristics of patients with infectious diarrhea have changed during the last decade in Shanghai. Methodology: The records of 29,210 patients with infectious diarrhea in the outpatient department of the Jinshan Hospital (Shanghai, China) between January 1998 and December 2013 were analyzed. Results: A total of 2,849 samples were positive for intestinal pathogenic bacteria including Vibrio parahaemolyticus (2,489; 84.0%), Salmonella spp. (235; 8.3%), and Shigella spp. (125; 4.4%). V. parahaemolyticus infections are mainly characterized by abdominal pain, nausea, and vomiting, whereas Shigella spp. infections can, in addition, induce fever. In contrast, Salmonella infections can produce all of these symptoms but in a smaller percentage of patients. During the 16-year study, both the number of patients and the positive infection rate declined. Notably, the rate of infections by V. parahaemolyticus decreased while the detection rates of Salmonella spp. increased year by year from 2006 on with the introduction of a new detection method. Conclusions: Salmonella has been identified as the third-most frequent cause of diarrhea from 1998–2006, as the second-most frequent cause from 2006–2010, and as the most frequent cause from 2011–2013, which was mainly due to a sharp decrease of V. parahaemolyticus infections in 2011–2013. Salmonella strains collected in 2011–2013 showed high susceptibility to imipenem (100%) and meropenem (100%), whereas susceptibilities for ampicillin (39%) and piperacillin (40%) were low.